2020
DOI: 10.2147/rmhp.s277846
|View full text |Cite
|
Sign up to set email alerts
|

<p>Knowledge, Attitudes and Practices Toward Prevention and Early Detection of COVID-19 and Associated Factors Among Religious Clerics and Traditional Healers in Gondar Town, Northwest Ethiopia: A Community-Based Study</p>

Abstract: Background: COVID-19 control measures efforts are affected by the knowledge, attitudes, and practices of the public, particularly religious clerics and traditional healers, who have close contact and are widely accepted by a significant number of community members. Methods: A community-based cross-sectional study was conducted to determine knowledge, attitudes and practices towards COVID-19 and its associated factors among religious clerics and traditional healers in Gondar town. Study participants who met our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
43
4
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(57 citation statements)
references
References 33 publications
9
43
4
1
Order By: Relevance
“…The included studies were all conducted in sub-Saharan Africa and published in 2020. Ten of the studies were conducted in Ethiopia [10,12,[29][30][31][32][33][34][35][36], eight in Nigeria [37][38][39][40][41][42][43][44], three in Cameroon [45][46][47], two in Uganda [9,48], one each in Rwanda [49], Ghana [50], Democratic Republic of Congo [51], Sudan [52], and Sierra Leone [53], (Fig 2). A total number of 14,353 study participants were reported in the included studies, with over half (51%) of them being males.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The included studies were all conducted in sub-Saharan Africa and published in 2020. Ten of the studies were conducted in Ethiopia [10,12,[29][30][31][32][33][34][35][36], eight in Nigeria [37][38][39][40][41][42][43][44], three in Cameroon [45][46][47], two in Uganda [9,48], one each in Rwanda [49], Ghana [50], Democratic Republic of Congo [51], Sudan [52], and Sierra Leone [53], (Fig 2). A total number of 14,353 study participants were reported in the included studies, with over half (51%) of them being males.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…The KAP components of the included studies (Fig 3), showed that participants from 24 studies had a good knowledge [9, 10, 29-32, 34-46, 48-50, 52, 53], with only 4 studies reporting a low knowledge of COVID-19 [12,33,47,51]. Participants in fifteen studies had a good attitude/perception [29, 34-37, 41-49, 52], average in five studies [10,12,33,40,53], and low in four studies [9,31,38,51]. Good preventative practice towards COVID-19 was found in twelve studies [9, 30, 36-38, 42, 43, 45, 46, 49, 50, 52], average in six [10,12,29,39,48,53], and low in other six studies [31-33, 35, 47, 51].…”
Section: Plos Onementioning
confidence: 99%
“…But our finding is comparable with the 66.6% and 56.6% study finding from northern Ethiopia. 13 The study findings also revealed that television (79%), radio (37%) and social media (31.6%) are the major sources of COVID-19 information. A study from the southern part of the country 16 also revealed that TV/radio is the major source (80.3%) of COVID-19 information.…”
Section: Discussionmentioning
confidence: 75%
“…This finding is much higher than other studies in the northern part of the country those reported 42.9% and 60.7% knowledgeable participants. 12 , 13 The variation might be explained by the difference in the characteristics of study participants, change in the study period, inadequate access to COVID-19 information and different knowledge measurement tools used by researchers. Though our study reveals a high level of knowledge among participants, the knowledge varies from one coronavirus transmission and prevention method to another.…”
Section: Discussionmentioning
confidence: 99%
“…We have read the paper by Asmelash et al 1 with great interest. In Pakistan, the religious pundits enjoy a huge following as well, coherent with this fact we would like to share our viewpoint towards the study.…”
mentioning
confidence: 99%